2008
DOI: 10.3324/haematol.11740
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporiosis in patients with acute leukemia: a retrospective multicenter report

Abstract: We retrospectively analyzed 542 proven/probable mould infections registered, in the course of 2 studies, in 8,633 patients with acute leukemia, focusing on scedosporiosis. We aimed to define scedosporiosis incidence and mortality rate over a 15-year period. Only 5 cases of scedosporiosis were identified, all of them involving patients with acute myeloid leukemia (AML). We also reviewed all cases of Scedosporium spp. infections in acute leukemia reported to date in the international literature. The 52 cases ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
0
22
0
5
Order By: Relevance
“…İlk hastaların tanımlanmasından günümüze kadar geçen sürede, yeni antifungal ilaçların kullanıma girmesine rağmen, skedosporyoz tedavisinde önemli bir başarı sağlanamamıştır. AML hastalarındaki uzun süreli immünsüpresyon, hızlı ve etkili antifungal tedaviyi gerektirmektedir 5 . Yaygın skedosporyozda etkin bir tedavi bulunmamaktadır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…İlk hastaların tanımlanmasından günümüze kadar geçen sürede, yeni antifungal ilaçların kullanıma girmesine rağmen, skedosporyoz tedavisinde önemli bir başarı sağlanamamıştır. AML hastalarındaki uzun süreli immünsüpresyon, hızlı ve etkili antifungal tedaviyi gerektirmektedir 5 . Yaygın skedosporyozda etkin bir tedavi bulunmamaktadır.…”
Section: Discussionunclassified
“…AML hastalarında kültürle varlığı gösterilen skedosporyoz insidansı %0.08 olarak rapor edilmiştir 5 . AML hastalarında görülen skedosporyozun klinik tablosu, daha sık enfeksiyon etkeni olan diğer filamentöz mantar enfeksiyonlarını taklit edebilmektedir.…”
Section: Introductionunclassified
“…Concerning the incidence of scedosporiosis among a certain disease status, Caira et al (11) reported the incidence of Scedosporium infections in patients with acute leukemia in Italy. They collected a total of 542 proven/probable mold infections among 8,633 patients with acute leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…La patogenia y la epidemiología de estas micosis emergentes es peor conocida, y su diagnóstico, más complicado, ya que no tienen unas características clínicas y radiológicas específicas y muchos de estos hongos poseen propiedades fisiológicas y relacionadas con el cultivo poco conocidas, lo que plantea dificultades para su identificación en el laboratorio 1,[7][8][9]39 .…”
Section: State Of the Art In Invasive Diseases By Filamentous Fungiunclassified
“…Posaconazol es una alternativa terapéutica en los casos en los que no es efectivo el tratamiento anterior (tabla 3). Lomentospora prolificans (Scedosporium prolificans) es un hongo multirresistente a los antifúngicos habituales y para su tratamiento se requiere la combinación de voriconazol con otros fármacos (terbinafina, una candina, miltefosina, colistina o interferón-␥), sin que pueda garantizarse un resultado satisfactorio 8,9,39 .…”
Section: Escedosporiasis Fusariosis Y Otras Micosis Por Hongos Filamunclassified